Use of the near vacuum UV spectral range for the analysis of W-based materials for fusion applications using LIBS. (21st January 2016) - Pribula, M; Krištof, J; Suchoňová, M; Horňáčková, M; Plavčan, J; Hakola, A; Veis, P
Abstract: The vacuum UV (VUV)-near Infrared (NIR) laser induced breakdown spectroscopy (LIBS) technique was applied to investigate the composition of W-based samples with a protective carbon layer. The sample was analyzed under pressures from 5 to 10 5 Pa and atmosphere (air, He). The spectra were recorded with three spectrometers at delays from 200 ns to 10 μ s at atmospheric pressures and from 100 to 500 ns at low pressures. The electron density was determined from the measured spectra using Stark broadening and the electron temperature from the W I–W III Saha–plot in the VUV–NIR spectral range. The better precision was achieved due to usage W III spectral lines of tungsten. The achieved results are more reliable than results obtained without W III spectral lines. The calibration free LIBS method was then applied to determine the W and C contents of the analyzed sample.